Significant Quantitative Differences in Orexin Neuronal Activation After Pain Assessments in an Animal Model of Sickle Cell Disease - Richardson, Kimberlei; Sweatt, Nia; Tran, Huy; Apprey, Victor; Uthayathas, Subramaniam; Taylor, Robert; Gupta, Kalpna (Frontiers in Molecular Biosciences, 2020)
Sickle cell disease is a hemoglobinopathy that causes sickling of red blood cells, resulting in vessel blockage, stroke, anemia, inflammation and extreme pain. The development and treatment of pain, in particular, neuropathic pain in sickle cell disease patients is poorly understood and impedes our progress towards the development of novel therapies to treat pain associated with sickle cell disease. The orexin/hypocretin system offers a novel approach to treat chronic pain and hyperalgesia. These neuropeptides are synthesized in three regions: perifornical area (PFA), lateral hypothalamus (LH) and dorsomedial hypothalamus (DMH). Data suggest that orexin–A neuropeptide has an analgesic effect on inflammatory pain and may affect mechanisms underlying the maintenance of neuropathic pain. The purpose of this study was to determine whether there are neuronal activation differences in the orexin system as a result of neuropathic pain testing in a mouse model of sickle cell disease. Female transgenic sickle mice that express exclusively (99%) human sickle hemoglobin (HbSS-BERK) and age-/gender-matched controls (HbAA-BERK mice; n = 10/group, 20-30g) expressing normal human hemoglobin A were habituated to each test protocol and environment before collecting baseline measurements and testing. Four measures were used to assess pain-related behaviors: thermal/heat hyperalgesia, cold hyperalgesia, mechanical hyperalgesia, and deep-tissue hyperalgesia. Hypothalamic brain sections from HbAA-BERK and HbSS-BERK mice were processed to visualize orexin and c-Fos immunoreactivity and quantified. The percentage of double labeled neurons in the PFA was significantly higher than the percentage of double labeled neurons in the LH orexin field of HbAA-BERK mice (*p<0.05). The percentages of double labeled neurons in PFA and DMH orexin fields are significantly higher than those neurons in the LH of HbSS mice (*p<0.05). These data suggest that DMH orexin neurons were preferentially recruited during neuropathic pain testing and a more diverse distribution of orexin neurons may be required to produce analgesia in response to pain in the HbSS-BERK mice. Identifying specific orexin neuronal populations that are integral in neuropathic pain processing will allow us to elucidate mechanisms that provide a more selective, targeted approach in treating of neuropathic pain in sickle cell disease.